Arbitration Mechanisms in Settlement of Maritime Disputes in Nigeria: Challenges and Prospects - Babatunde, Ekundayo O (Faculty of Law, Universitas Brawijaya, 2019)
The maritime industry is globally recognized as one of the most economically viable industry capable of facilitating sustainable development thus, amicable settlement of maritime disputes is paramount to guarantee unhindered trade and commerce environment. Arbitration is an age-long Alternative Dispute Resolution (ADR) mechanism applied in the amicable settlement of disputes in a relaxed and semi-formal environment. It is particularly suitable for resolving commercial disputes because of the enforceability of arbitral awards as depicted by the existing international arbitral jurisprudence. Various law of the Sea tribunals such as the International Tribunal for the Law of the Sea (ITLOS) or an ad hoc panels expressly recognizes arbitration as one of the models for settlement of disputes as a suitable alternative to litigation. In Africa, as nations recover from the era of ocean blindness, maritime practice and administration is prioritized to aid economic growth. The objective of this study is to evaluate application of arbitration as an ADR mechanism for settling maritime disputes in Nigeria’s maritime practices with the aim of identifying the challenges confronting Nigerian’s involvement in maritime business, particularly as it relates to application of Arbitration to dispute settlement. It was found that there are certain loopholes in relevant laws which work hardship against local businesses in cases of maritime disputes settlement. The study suggests viable solutions based on lessons from other climes to create level playing field for parties who opt for arbitration to settle maritime related disputes.